Rising incidence of acute pancreatitis in Sweden: National estimates and trends between 1990 and 2013. Issue 4 (May 2020) - Oskarsson, Viktor; Hosseini, Servah; Discacciati, Andrea; Videhult, Per; Jans, Anders; Ekbom, Anders; Sadr-Azodi, Omid
Background: Recent reports from western countries have indicated an increased incidence and a decreased mortality in acute pancreatitis. However, the incidence assessment has often been hampered by the inclusion of both first-time and recurrent episodes of acute pancreatitis. Methods: In this retrospective cohort study, all Swedish residents hospitalized with a first-time episode of acute pancreatitis between 1990 and 2013 were identified using national registers. Sex- and age-standardized incidence rates per 100, 000 individuals and year were calculated, as were annual percent changes (APC) from joinpoint regression models. Results: Overall, between 1990 and 2013, 66, 131 individuals had a first-time episode of acute pancreatitis in Sweden. Comparing the first five years (1990–1994) to the last four years (2010–2013) of the study period, the overall incidence of acute pancreatitis increased from 25.2 (95% confidence interval (CI): 24.1, 26.3) to 38.3 (95% CI: 37.0, 39.5) cases per 100, 000 individuals and year. An increase in incidence was observed irrespective of the subtypes of acute pancreatitis as well as the sex and age of the patients. Although the incidence of complicated acute pancreatitis declined in both men and women between 1990 and 2004, it started to increase in both sexes (APC 3.0; 95% CI: 0.5, 5.5 in men; APC 5.4; 95% CI: 2.6, 8.2 in women) from 2005 onwards. Conclusion: Based on nationwide data, the incidence of first-time acute pancreatitis has increased in Sweden over a period of 24 years. The incidence of disease-related complications has also been on the rise during the past few years, after declining for more than 15 years before that.